THE GUISES OF REPLACEMENT COST. - Coughlan, John W. (The Accounting Review, 1957)
Abstract Believing that financial statements could not serve managerial, tax and regulatory purposes well unless they were adjusted for price changes, accountants have, particularly during the last quarter century, been anxious to employ replacement cost in the calculation of income. On the other hand, they have been reluctant to depart from the original monetary outlay for assets, that is, from cost incurred. The compromise has been to present replacement cost so that it appeared to adhere to cost incurred. The last-in first-out, or LIFO, method of inventory pricing is a good example. The LIFO implies a departure from cost incurred in favor of replacement cost or current cost. Nevertheless, the departure has been accomplished in such a manner that students of inventory accounting are apparently convinced that no departure from cost incurred is involved. The contrast between the conventional first-in first-out, or FIFO, calculation of cost of sales and the LIFO calculation has been discussed in this article with an example.